Experimental study of a novel mouse model of tibial shaft fracture combined with blunt chest trauma - Bing Zhang; Tingting Fu; Yi Han; Gongke Li; Xianyao Wan; Yong Li (Animal Models and Experimental Medicine)
Abstract Backgroud Thoracic Trauma and Limb Fractures Are the Two most Common Injuries in Multiple Trauma. However, there Is Still a Lack of Mouse Models of Trauma Combining Tibial Shaft Fracture (TSF) and Thoracic Trauma. In this Study, we Attempted to Develop a Novel Mouse Model of TSF Combined with Blunt Chest Trauma (BCT). Methods A total of 84 C57BL/6J male mice were used as the multiple trauma model. BCT was induced by hitting the chests of mice with heavy objects, and TSF was induced by hitting the tibia of mice with heavy objects after intramedullary fixation. Serum specimens of mice were received by cardiac puncture at defined time points of 0, 6, 12, 24, 48, and 72 h. Results Body weight and body temperature tended to decrease within 24 h after multiple trauma. Hemoglobin analyses revealed a decrease during the first 24 h after multiple trauma. Some animals died by cardiac puncture immediately after chest trauma. These animals exhibited the most severe pulmonary contusion and hemorrhage. The level of lung damage varied in diverse mice but was apparent in all animals. Classic hematoxylin and eosin (H&E)‐stained paraffin pulmonary sections of mice with multiple trauma displayed hemorrhage and an immunoinflammatory reaction. Bronchoalveolar lavage fluid (BALF) and serum samples of mice with multiple trauma showed an upregulation of interleukin‐1β (IL‐1β), IL‐6, and tumor necrosis factor‐1α (TNF‐1α) compared with the control group. Microimaging confirmed the presence of a tibia fracture and pulmonary contusion. Conclusions The novel mouse multiple trauma model established in this study is a common trauma model that shows similar pathological mechanisms and imaging characteristics in patients with multiple injuries. This study is useful for determining whether blockade or intervention of the cytokine response is beneficial for the treatment of patients with multiple trauma. Further research is needed in the future.